EFEKTIVITAS UNDANG-UNDANG NOMOR 3 TAHUN 2006 TENTANG PERADILAN AGAMA TERHADAP KESIAPAN PENGADILAN AGAMA TULANG BAWANG MENANGANI PERKARA EKONOMI SYARI’AH - Khasanah, Mita; Chintya, Aprina (Universitas Islam Negeri Raden Fatah Palembang, 2017)
Since the appearance of the law No. 3 of 2006 on the Religious Courts twelve years ago, the Religious Courts Tulang Bawang have done a lot of efforts in the face of economic matters of Shariah, including the preparation of the competence of judges in sharia economic settlement to the case, given the judge in the Religious always transferred from one court to another court. This study seeks the effectiveness of Law No. 3 of 2006 on religious court of the readiness of the Religious Courts dealing with cases of economic Tulang Bawang Shari'ah. This is a descriptive field research. Datacollection techniques in this study were interviews and documentation. After the data were obtained, the data were then analyzed inductively. Based on the results of the study, Law No. 3 of 2006 on the Religious Courts has been effective in preparing readiness of Tulang Bawang Religious Courts dealing with cases of Shari'ah economic disputes.This is evidence from the judges in the Religious Tulang Bawang who always participated in the seminar, diktat and training in order to enhance the competence of the judges in resolving the case in religious courts. And these are continuesly done by Religious Courts Tulang Bawang because; there is always a judge who comes in and out of themutation of the religious courts.